The loss of left atrial contractile function predicts a worse outcome in HFrEF patients - Mandoli, Giulia Elena; Pastore, Maria Concetta; Benfari, Giovanni; Setti, Martina; Maritan, Luca; Diviggiano, Enrico Emilio; D’Ascenzi, Flavio; Focardi, Marta; Cavigli, Luna; Valente, Serafina; Cameli, Matteo (Frontiers in Cardiovascular Medicine, 2023)
Background In chronic heart failure, high intracardiac pressures induce a progressive remodeling of small pulmonary arteries up to pulmonary hypertension. At the end of left atrial conduit function, pulmonary and left heart end-systolic pressures equalization might affect left atrial systole. In this single-center prospective study, we aimed to investigate whether peak atrial contraction strain (PACS), measured by speckle tracking echocardiography, was independently associated with prognosis in heart failure with reduced ejection fraction (HFrEF). Materials and methods Outpatients with HFrEF and sinus rhythm referred to our echo-labs were enrolled. After clinical and echocardiographic evaluation, off-line speckle tracking echocardiography analysis was performed. Primary and secondary endpoint were cardiovascular death and heart failure hospitalization, respectively. Spline knotted survival model identified the optimal prognostic cut-off for PACS. Results The 152 patients were stratified based on PACS <8% (n = 76) or PACS ≥8% (n = 76). Patients with PACS <8% had lower left ventricle and left atrial reservoir strain and higher New York Heart Association (NYHA) class and left atrial volume index (LAVI). Over a mean follow-up of 3.4 ± 2 years, 117 events (51 cardiovascular death, 66 heart failure hospitalizations) were collected. By univariate and multivariate Cox analysis, PACS emerged as a strong and independent predictor of cardiovascular death and heart failure hospitalization, after adjusting for age, sex, left ventricle strain, and E/e’, LAVI (HR 0.6 per 5 unit-decrease in PACS). Kaplan–Meier curves showed a sustained divergence in event-free survival rates for the two groups. Conclusion The reduction of PACS significantly and independently affects cardiovascular outcome in HFrEF. Therefore, its assessment, although limited to patients with sinus rhythm, could offer additive prognostic information for HFrEF patients.